Osmanlı arşiv vesikalarına göre XIX. asırda Uşak vakıf hizmetleri - Arıkan, Abdülhakim (My University, 2005)
Bulunduğu Coğrafî konum itibârıyla Ege ve İç Anadolu kültürünün ortak özelliklerini taşıyan bugünkü Uşak ili, Osmanlı devrinde Kütahya sancağına bağlı bir kazâdır. Arşiv vesîkalarını esas alarak yapılan bu araştırmada, XIX. asırda Uşak ve civârındaki câmi', mektep, medrese, tekke ve zâviye nevinden müesseseleri ele alınmıştır. Osmanlı Arşiv vesîkalarında tesbît edilmiş câmi' sayısı 28, medrese ve mektep sayısı 7, tekke ve zâviye sayısı 50'dir. XIX. asırda Uşak ve nâhiyelerindeki vakıf hizmetlerinin umûmî bir görüntü tesbît edilerek, Uşak'ın târihinde bir vakıf şehri oluğu yapılan çalışmadan anlaşılmaktadır. As respects to its geographical position, the city of Uşak, which bears comman features of Aegean and Interior Anatolian Culture, was a district of Kütahya sanjak in the Otoman period, This research that is based on certificates of Otoman Archives, deals with foundations such as mosques, schools ( mektep ), medresseh, tekke and some small devrish lodpes ( Zâviye ) at the surrounding of Uşak in 19.th century in this study, the number of mosques and small mosques 28, the number of medressehs and schools ( mektep ) are 7, the number of tekke and small dervish lodges ( zâviye ) are 50 which are ascertained from the certificates of Otoman archives. The general Picture of waqf's function, at Uşak and its subdistricts in 19 th century, is determined in this study. All the data shows that Uşak has been a city that had the all kind of function.
Keywords: Vakıflar